1. Not finding help here? Sign up for a free 30min tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Helmholtz Energy Proof (thermodynamics)

  1. Sep 19, 2013 #1
    1. The problem statement, all variables and given/known data
    Define the Helmholtz free energy as F=E-TS.
    Show that the internal energy E=-T2[itex]\frac{∂}{∂T}[/itex]([itex]\frac{F}{T}[/itex])V

    2. Relevant equations
    S=([itex]\frac{∂F}{∂T}[/itex])V

    Perhaps [itex]\beta[/itex]=[itex]\frac{1}{\tau}[/itex]
    and [itex]\tau[/itex]=kBT

    3. The attempt at a solution
    E = F+TS
    E = F+T([itex]\frac{∂F}{∂T}[/itex])V
    .
    .
    . (some steps to final equation)
    .
    .
    E=-T2[itex]\frac{∂}{∂T}[/itex]([itex]\frac{F}{T}[/itex])V


    Any help/hints would be greatly appreciated. My partial derivatives are a bit rusty. Thanks
     
  2. jcsd
  3. Sep 19, 2013 #2

    TSny

    User Avatar
    Homework Helper
    Gold Member

    Note [itex]\frac{∂}{∂T}[/itex]([itex]\frac{F}{T}[/itex])V = [itex]\frac{∂}{∂T}[/itex]([itex]\frac{1}{T} \cdot F)[/itex]V and use the product rule to write out the partial derivative.

    Also, check to see if there's a sign error in your equation S=([itex]\frac{∂F}{∂T}[/itex])V
     
  4. Sep 21, 2013 #3
    Okay! I got it..

    So

    E=-T2[-[itex]\frac{1}{T^2}[/itex]F + [itex]\frac{∂F}{∂T}[/itex][itex]\frac{1}{T}[/itex]]

    E= F + ([itex]\frac{∂F}{∂T}[/itex])(-T)
    E= F+(-S)(-T)
    E= F+TS

    F=E-TS

    Thank you!!
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted



Similar Discussions: Helmholtz Energy Proof (thermodynamics)
  1. Helmholtz free energy (Replies: 10)

Loading...